Blue Economy - Germond-Duret, Celine; Garland, Michaela; Heidkamp, C. Patrick; Morrissey, John (International Encyclopedia of Geography, 2016)
Geography has engaged in insightful discussions on how to understand, analyze, criticize, and implement the blue economy. United Nations agencies, Small Island Developing States, and increased academic interest in oceans have played important roles in the global adoption of the blue economy idea, that is, the sustainable exploitation of marine and coastal resources. Geographical research on the blue economy has addressed key themes such as economic and political discourse, relational thinking and assemblage, sustainability and just transitions, and blue economy risks.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118786352.wbieg2166
Keywords: coastal and marine geography; dept.egm; economic development; environmental management; sustainable development

The Kyrgyz Republic,1 central Asia, and daily life engagement - Yacher, L. (Arab World Geographer, 2016)
Keywords: Central Asia; Kyrgyzstan; dept.egm; geographical thought; life satisfaction; perception; ⛔ No DOI found

The role of magnetic agents in shaping post-disaster land use - Zavar, Elyse (Land Use Policy, 2016)
Three neighborhoods in Lexington, Kentucky, share a common flood history, including property acquisitions, as a means to mitigate against flooding; yet, the interactions of residents with the buyout landscapes vary significantly among the neighborhoods. Although the same institutions and structural controls implemented flood buyout programs in all three neighborhoods, semi-structured interviews illustrate that differing perspectives, personalities, and neighborhood politics shaped unique identities and land uses for the acquired properties in each neighborhood. Varying levels of resident engagement with the buyout landscape resulted in a range of attitudes towards hazard preparation, management, and mitigation, thus leaving some neighborhoods more resilient to future flooding than others. This study explores key residents, termed magnetic agents, who drove neighborhood civic action and land uses on the open space created through floodplain property acquisition. This research indicates magnetic agents can serve as important partners for local governments and non-governmental organizations (NGOs) in building community-based projects aimed at reducing vulnerability to flood events and instituting high utility land uses on floodplain buyout open space.(C) 2016 Elsevier Ltd. All rights reserved.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-794-376-727-198 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Agency; Floodplain buyout; Kentucky; Land management; Lexington; Resiliency; United States; dept.egm; flooding; floodplain; hazard management; land management; land use planning; neighborhood; open space

The Modifiable Conceptual Unit Problem demonstrated using pollen and seed dispersal - Miller, Matthew D (Global Ecology and Conservation, 2016)
The Modifiable Areal Unit Problem (MAUP) is a famous issue in spatial analysis that states the output of a spatial analysis is influenced by the spatial extent of the units used in the analysis. This study demonstrates that the MAUP is accompanied with another intractable spatial issue in spatial modeling; the Modifiable Conceptual Unit Problem (MCUP). The MCUP states that the conceptualization of spatial processes impacts the output of spatial analysis and occurs when a model with one spatial dimension is applied to a spatial model with more than one spatial dimension. This study demonstrates the MCUP by developing three conceptual models of dispersal and showing how they produce different results even when given the same initial dispersal curves and areal units. Three conceptual models of dispersal (sum of curve points model, area of distance range model, and the volume of distance range model) are described and applied to a grid landscape with a single point of dispersal and a grid landscape with multiple points of dispersal. A Geographic Information System (GIS) is used to evaluate how the models differ in their distribution of pollen or seeds across the landscapes. The three models of dispersal are each valid conceptualizations of the dispersal process, but when given the same dispersal curve parameters, they produce different distributions of dispersed items across grid landscapes. The sum of curve points model is the least complicated model because it only uses a few points from the defined dispersal curve. The area of distance range model uses the entire dispersal curve, but is based on a single dimension of space and thus conceptually abstracted from the grid landscape. The volume of distance range model uses the two spatial dimensions present in the grid landscape and thus is the most conceptually sound model of the three. The underlying conceptualization of the dispersal process can impact the results of dispersal models. Applying dispersal curves with one spatial dimension to grids with two spatial dimensions makes inherent assumptions about the conceptualization of dispersal. This study highlights the necessity of researchers to declare their conceptual models of dispersal when applying modeled dispersal curves to grid landscapes. © 2016 The Author.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-510-462-186-063 tex.type: [object Object]
Keywords: Conceptual; Dispersal; Grid; MAUP; Pollen; Spatial; dept.egm

Land use change on US floodplain buyout sites, 1990-2000 - Zavar, Elyse; Hagelman, III, Ronald R. (Disaster Prevention and Management, 2016)
Purpose - The Federal Emergency Management Agency provides guidelines for the management of open space created through property acquisition (buyouts); however, land use decisions are primarily left to local governments manifesting in a variety of uses. The purpose of this paper is to provide a land use assessment of buyout sites, to describe the changes in those uses that have occurred during a ten-year period from 1990 to 2000, and to offer an assessment of management approaches employed across these sites. Design/methodology/approach - Using a mixed-methods approach consisting of a land use classification survey and a semi-structured questionnaire of floodplain managers, this study explores the land use trends at buyout sites, diverse approaches local governments take in managing the open spaces created through floodplain buyout programs, and the successes and challenges communities face in open space management. Findings - Results indicate strong support from floodplain managers for property acquisition and several cases emerged where communities put their newly acquired public land to creative uses. However, the opportunity to leverage these properties for greater public values is largely being missed, primarily because of limited funding. Practical implications - The analysis indicates strong support among floodplain managers for the buyout approach; however, additional resource-sharing and funding opportunities are needed to increase the utility of buyout properties. Originality/value - By evaluating the long-term management strategies floodplain managers utilize on buyout sites, this study adds to an underrepresented area of scholarship and is of value to practitioners, government officials, and academics.
44 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-423-912-140-83X tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Buyout; Disaster mitigation; Floodplain management; Land use; dept.egm